Political Traditions and UK Politics - Hall, M. author. aut Link
X, 272 p.
Keywords: An exploration of political traditions and their usage in explanations of British politics. This book includes an evaluation of both classical and critical approaches to the British Political Tradition. It also analyses more recent uses of political tradition by Bevir, Rhodes and Marquand.